2020
DOI: 10.1021/acs.jpcc.0c04440
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Defects on WSe2

Abstract: The 2D nature of transition metal dichalcogenides (TMDs) makes their electronic and optical performance highly susceptible to the presence of defects. At elevated temperatures, which can be reached during growth or in operation, additional defects can be introduced and lead to further material degradation. Therefore, by studying the impact of temperature on 2D-TMDs, the formation of defects and their respective degradation pathways can be established. The electronic and geometric structure and density of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Interestingly, the simulated curve for 2 × 10 11 cm –2 surface doping shows a good match with our experimental results (black symbols), suggesting that unpassivated devices may have some fixed positive charge at the surface that causes electrons in WSe 2 to accumulate near the surface to maintain charge neutrality at the interface. These positive fixed charges are likely due to selenium vacancies , induced on the surface during our 350 °C annealing step during fabrication. The simulated curves also show that increases in positive surface charge lead to large improvements in photocurrent collection away from the top electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the simulated curve for 2 × 10 11 cm –2 surface doping shows a good match with our experimental results (black symbols), suggesting that unpassivated devices may have some fixed positive charge at the surface that causes electrons in WSe 2 to accumulate near the surface to maintain charge neutrality at the interface. These positive fixed charges are likely due to selenium vacancies , induced on the surface during our 350 °C annealing step during fabrication. The simulated curves also show that increases in positive surface charge lead to large improvements in photocurrent collection away from the top electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Blades et al studied the electronic band structure and defect density of 2D WSe 2 before and after annealing by using STM/STS. [ 98 ] They found that the bandgap distribution was significantly broadened because of a seven‐fold increase in defect density and the introduction of n ‐type and p ‐type defect after 600 °C annealing, as shown in Figure ,b. Four different types of defects were identified (Figure 6c,e).…”
Section: Lateral Heterojunctionmentioning
confidence: 97%
“…From the scanning tunnelling spectroscopic (STS) measurements, it is observed that an asymmetry exists between the valence band maximum and conduction band maximum, with respect to the Fermi level, revealing slightly n-type doping of the grown WSe 2 films. In another report, Blades et al 86 have comprehensively studied the electronic and geometric structure of defects in WSe 2 thin films grown on highly oriented pyrolytic graphite (HOPG) with STS and STM, and the effect of temperature on the nature of these defects. In 2018, Wang et al 87 reported the transport properties of highly crystalline epitaxial TiSe 2 thin films on a sapphire substrate grown by MBE.…”
Section: Recent Advances In Mbe-grown Transition Metal Dichalcogenidesmentioning
confidence: 99%